The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013 IEEE Photonics Conference 2013
DOI: 10.1109/ipcon.2013.6656387
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and applications of InGaN micro-light emitting diodes on Si substrates

Abstract: InGaN micro-light emitting diodes on Si substrates have been fabricated and characterized. Their abilities for micro-display, high modulation bandwidth of 270 MHz and data transmission rate of up to 400 Mbit/s have been demonstrated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…In 2004, M. D. Dawson et al reported the fabrication process and performance of a 64 × 64 array of ultraviolet (UV) micro-LEDs with a diameter of about 20 μm 21 . K. M. Lau and Z. J. Liu et al reported on UV and red, green, and blue (RGB) micro-LEDs with a diameter of 50 μm and 360 pixels per inch (PPI) resolution in 2013 22 , and then on blue micro-LEDs with 1700 and 2500 PPI resolution displays 23,24 . In 2014, P. F. Tian et al fabricated 10 × 10 micro-LED arrays with pixel diameters of 45 μm and peak emission at ~470 nm 25 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, M. D. Dawson et al reported the fabrication process and performance of a 64 × 64 array of ultraviolet (UV) micro-LEDs with a diameter of about 20 μm 21 . K. M. Lau and Z. J. Liu et al reported on UV and red, green, and blue (RGB) micro-LEDs with a diameter of 50 μm and 360 pixels per inch (PPI) resolution in 2013 22 , and then on blue micro-LEDs with 1700 and 2500 PPI resolution displays 23,24 . In 2014, P. F. Tian et al fabricated 10 × 10 micro-LED arrays with pixel diameters of 45 μm and peak emission at ~470 nm 25 .…”
Section: Introductionmentioning
confidence: 99%